Efficacy and Safety of Adalimumab in Noninfectious Uveitis: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Li, Biao; Li, Haoran; Zhang, Li; Zheng, Yanlin (Frontiers in Pharmacology, 2021)
Abstract Background: Patients with non-infectious uveitis (NIU) are at risk of systemic side effects of long-term glucocorticoid therapy and uncontrolled inflammatory complications. An urgent need to identify more aggressive therapies, and adalimumab (ADA) may be the right choice. Objectives: To summarise the current evidence from randomised controlled trials (RCTs) regarding the efficacy and safety of ADA in the treatment of NIU. Methods: We searched Pubmed, Embase, Web of Science, Cochrane Library databases, and ClinicalTrialsRegistry for qualifying articles from their inception to November 19, 2020, with no language restriction. Randomised controlled trials comparing ADA with conventional routine treatment in non-infectious uveitis patients of any age, gender, or ethnicity were included. The primary outcome was the time to treatment failure (TF). The secondary outcomes were the change in best-corrected visual acuity (BCVA), change in the anterior chamber(AC) cell grade, change in vitreous haze(VH) grade, and adverse events(AEs). Main results: The six studies comprised 605 participants in all, and the sample size of each study ranged from 16 to 225. The overall pooled results of the primary outcome (HR=0.51; 95%CI, 0.41-0.63) showed that ADA nearly halved the risk of treatment failure compared to placebo for NIU patients. The pooled mean difference of change in BCVA was -0.05 (95%CI, -0.07 to -0.02). The pooled mean difference of change in AC cell grade and VH grade was -0.29 (95%CI, -0.62 to -0.05) and -0.21( 95%CI, -0.32 to -0.11), respectively. The incidence of AEs in the ADA group was numerically higher than that in the placebo group (2237 events and 9.40 events per patient-year, equivalent to 1257 events and 7.79 events per patient-year). Conclusion: This meta-analysis of seven RCTs further confirmed that ADA considerably lowered the risk of treatment failure or visual loss, moderately reduced AC cell grades and VH grades with slightly more AEs, as compared to placebo. ADA is both effective and safe in treating NIU. Systematic review registration number: CRD42020217909